Epinephrine extensively changes the biofilm matrix composition in Micrococcus luteus C01 isolated from human skin - Gannesen, Andrei V.; Ziganshin, Rustam H.; Zdorovenko, Evelina L.; Klimko, Alena I.; Ianutsevich, Elena A.; Danilova, Olga A.; Tereshina, Vera M.; Gorbachevskii, Maxim V.; Ovcharova, Maria A.; Nevolina, Ekaterina D.; Martyanov, Sergey V.; Shashkov, Alexander S.; et al. (Frontiers in Microbiology, 2022)
The importance of the impact of human hormones on commensal microbiota and microbial biofilms is established in lots of studies. In the present investigation, we continued and extended the research of epinephrine effects on the skin commensal Micrococcus luteus C01 and its biofilms, and also the matrix changes during the biofilm growth. Epinephrine in concentration 4.9 × 10-9 M which is close to normal blood plasma level increased the amount of polysaccharides and extracellular DNA in the matrix, changed extensively its protein, lipid and polysaccharide composition. The Ef-Tu factor was one of the most abundant proteins in the matrix and its amount increased in the presence of the hormone. One of the glucose-mannose polysaccharide was absent in the matrix in presence of epinephrine after 24 h of incubation. The matrix phospholipids were also eradicated by the addition of the hormone. Hence, epinephrine has a great impact on the M. luteus biofilms and their matrix composition, and this fact opens wide perspectives for the future research.